2006
DOI: 10.2174/092986706776360842
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-Induced Gastric Ulceration: Protection By Melatonin

Abstract: Gastric hyperacidity and ulceration of the stomach mucosa due to various factors are serious health problems of global concern. Although the mechanism of acid secretion from the parietal cells is now well understood, the processes involved in gastric ulceration are still not clear. Among the various causes of gastric ulceration, lesions caused by stress, alcohol consumption, Helicobacter pylori and due to use of non-steroidal anti-inflammatory drugs have been shown to be mediated largely through the generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 131 publications
1
72
0
2
Order By: Relevance
“…Therefore, the main therapeutic target is the control of this secretion using antacids, H2 receptor blockers (ranitidine, famotidine) or proton pump blockers (omeprazole and lansoprazole) (Rao et al, 2004). However, nowadays, gastric ulcer therapy faces a major drawback because most of the drugs currently available in the market show limited efficacy against gastric diseases and are often associated with severe side effects (Bandyopadhyay et al, 2002;Lehne, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the main therapeutic target is the control of this secretion using antacids, H2 receptor blockers (ranitidine, famotidine) or proton pump blockers (omeprazole and lansoprazole) (Rao et al, 2004). However, nowadays, gastric ulcer therapy faces a major drawback because most of the drugs currently available in the market show limited efficacy against gastric diseases and are often associated with severe side effects (Bandyopadhyay et al, 2002;Lehne, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant potential of melatonin was found to be the reason for its anti-ulcer property by scavenging ROS. [36] Even though the present study shows significant ulceroprotective action of the extract of C. longa, its precise mechanism of action is not clear. Further studies are required to find out the actual mechanisms which leading to its antiulcer action.…”
Section: [31]mentioning
confidence: 54%
“…MEL may act as a potent free radical scavenger, by neutralizing hydroxyl and peroxyl radicals among others, preventing lipid membrane peroxidation, apoptosis, and protecting the DNA from the damage induced by free radicals. 18,19 The presented study has demonstrated that pre-treatment with Agomelatine protected the gastric mucosa from ulcer induction by absolute ethanol, and the protection of the gastric mucosa was morphologically improved when the doses were increased. The repair of ulcer damage requires a complete reestablishment of the connective tissue of the mucosa, the underlying submucosa, the re-formation of glandular architecture, and the growth of new blood vessels.…”
Section: Discussionmentioning
confidence: 72%